Can't We Do Better? A cost-benefit analysis of proposal writing in a competitive funding environment. - Gerald Schweiger (PLoS ONE, 2023)
This article presents an analysis of third-party funding in Austria for energy research, including an analysis of the costs and benefits of writing proposals and of the trust proposal applicants place in the application process. For this purpose, applicants from research and industry applying for government-funded energy research grants in Austria were surveyed. Preparing a new proposal takes about 50 working days; at the current success rate, about 300 person-days are spent preparing proposals for a single proposal to be funded.More than 90% of researchers perceive that they currently spend too much time preparing proposals and only 10% of researchers believe that the current competitive third-party funding system has a positive effect on the quality of research. Furthermore, researchers have limited trust in the objectivity of proposal review processes.